Contact dermatitis following use of tropical traditional medicine - Leelavathi Muthupalaniappen,; Teh Rohalia Jamil,; Chellathuray S, (Fakulti Perubatan, UKM, 2016)
Traditional or herbal medications are generally perceived as safe since it is derived from natural or plant sources. A rise in number of adverse reactions are being reported with the use of traditional medications including localized cutaneous reactions. The diagnosis of contact dermatitis is often quite straight forward based on its appearance, pattern, site and distribution of the lesion which usually corresponds to the area of contact. We report the case of a 65-year-old woman who presented with redness, burning sensation and swelling of her hand after applying topical Chinese traditional medication. This report aims to outline simple measures to identify and manage contact dermatitis secondary to topical medication. The present case creates awareness that topical traditional medications are not as harmless as previously thought to be. Precautions regarding adverse reactions are required, as those with conventional medications.